STRATEGI KOMUNIKASI PENYULUH AGAMA HINDU KANTOR KEMENTERIAN AGAMA KABUPATEN GIANYAR MELALUI MEDIA SOSIAL PADA MASA PANDEMI COVID-19 - Putu Agus Andita; I Gusti Ngurah Sudiana; I Wayan Sukabawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Hindu religious instructors are people who carry out their duties as interpreters or provide counseling to Hindus. The extension worker conducts coaching by gathering the community at the village hall, or at the temple in accordance with the target area. With the Covid-19 Pandemic, which forces people to stay at home and the rules issued by the government regarding the prohibition on gathering and gathering large numbers of people, of course, this makes it very difficult for extension workers to carry out their duties to provide guidance to Hindus in their target areas. each. The method used in this research is the interview method and also direct observation of the object of research as well as a study of the existing literature in the Hindu Guidance Section of the Ministry of Religion, Gianyar Regency. This research focuses on the strategies used by extension workers to continue carrying out their duties when the Covid-19 pandemic is hitting almost all countries in the world. The strategy used by the extension workers is through social media such as WhatsApp, Facebook, and through podcast broadcasts that are broadcast on the YouTube account of the Ministry of Religion of Gianyar Regency.